Indolizine–Squaraines: NIR Fluorescent Materials with Molecularly Engineered Stokes Shifts. Issue 51 (9th August 2017) - McNamara, Louis E.; Rill, Tana A.; Huckaba, Aron J.; Ganeshraj, Vigneshraja; Gayton, Jacqueline; Nelson, Rachael A.; Sharpe, Emily Anne; Dass, Amala; Hammer, Nathan I.; Delcamp, Jared H.
Abstract: The development of deep red and near infrared emissive materials with high quantum yields is an important challenge. Several classes of squaraine dyes have demonstrated high quantum yields, but require significantly red‐shifted absorptions to access the NIR window. Additionally, squaraine dyes have typically shown narrow Stokes shifts, which limits their use in living biological imaging applications due to dye emission interference with the light source. Through the incorporation of indolizine heterocycles we have synthesized novel indolizine squaraine dyes with increased Stokes shifts (up to >0.119 eV, >50 nm increase) and absorptions substantially further into the NIR region than an indoline squaraine benchmark (726 nm versus 659 nm absorption maxima). These materials have shown significantly enhanced water solubility, which is unique for squaraine dyes without water‐solubilizing substituents. Absorption, electrochemical, computational, and fluorescence studies were undertaken and exceptional fluorescence quantum yields of up 12 % were observed with emission curves extending beyond 850 nm. Abstract : Dying to fluoresce : Twelve novel squaraine dyes were prepared with an indolizine donor; they have molecularly engineered Stoke shifts and strong emissions in the NIR region (see scheme). Computational analysis is provided to aid in understanding these parameters.